Epicondylitis in the athlete`s albow - Van Hofwegen, C.; Baker, C. L. (Clinics in Sports Medicine, 2010)
Epicondylitis is a diagnostic term that describes a pattern of pain and tenderness localized to the medial or lateral epicondyles of the distal humerus. The pathoanatomy, clinical presentation, and treatment of these disorders is described. Nonoperative treatment, operative techniques, postoperative care, and the results of treatment are discussed.